Does Interbank Borrowing Reduce Bank Risk? - Valeriya Dinger; Jürgen von Hagen (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
In this paper we investigate whether banks that borrow from other banks have lower risk levels. We concentrate on a large sample of Central and Eastern European banks which allows us to explore the impact of interbank lending when exposures are long-term and interbank borrowers are small banks. The results of the empirical analysis generally confirm the hypothesis that long-term interbank exposures result in lower risk of the borrowing banks.
urn:nbn:de:bvb:19-epub-13329-0
Keywords: G21; E53; 330; interbank market; bank risk; market discipline; transition countries